Lexical Bundles in Academic Writing: The Issue of Specificity - Ang, Leng Hong (European Publisher, 2019)
The contextual knowledge of a word is closely related to the knowledge of phraseological sequences as words are often used in the phraseological forms. Owing to the importance of phraseological knowledge, much has been done to examine the phraseological sequences for various purposes, including for English for Academic Purposes (EAP). In EAP settings, scholars have argued for the two different approaches to EAP, i.e. discipline-specific and common-core. As such, it is necessary to examine the issue of specificity in EAP with regard to the use of phraseological sequences such as lexical bundles. This study therefore aims to identify lexical bundles in journal articles in the field of International Business Management (IBM). Following corpus-driven approach the corpus analysis software, Collocate 1.0 was used to extract three- to five-word combinations. These combinations were manually checked to exclude meaningless combinations. To determine to degree of specificity of the lexical bundles, the final lists of lexical bundles were compiled and compared with lexical bundles in Academic Formulas Lists (AFL) using log-likelihood test. The comparison reveals that lexical bundles in the IBM corpus are relatively specific as compared with the lexical bundles in AFL which are derived using common-core approach. A discipline-specific approach to the teaching and learning of lexical bundles in EAP settings is therefore advocated to enhance EAP syllabuses and instruction.